Public Health Interventions for COVID-19 Reduce Kawasaki Disease in Taiwan - Ya-Ling Yang; Ho-Chang Kuo (MDPI AG, 2021)
Background: Kawasaki disease (KD) is a syndrome of unknown cause that results in high fever and coronary vasculitis in children. The incidence of KD increased in Taiwan over the past few decades. Taiwanese government executed domains of early screening, effective methods for isolation or quarantine, and digital technologies for identifying potential cases for the early elimination strategy for coronavirus disease 2019 (COVID-19) and public health interventions for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or COVID-19 pandemic, leading to an effective reduction of the risk of airway infections in children. The purpose of this study is to analyze whether those public health interventions reduce the incidence of KD in 2020. Methods: Patients with KD who visited Chang Gung Memorial Hospital (CGMH) between 1 January, 2018, and 31 December, 2020 were included for trend analysis. This is a retrospective case series study conducted at the CGMH, which consists of a network of seven hospital branches equipped with more than 10,000 beds in different areas of Taiwan. Results: Compared with the 2018 and 2019 databases, the incidence of KD decreased significantly by 30% and 31%, respectively (p < 0.05) in 2020, when public health interventions were comprehensively implemented in Taiwan. This result shows that the incidence of KD decreased during the COVID-19 pandemic in Taiwan without change of the presentation KD (typical or incomplete) and percentage of IVIG resistance in 2020. Conclusion: As public health interventions were carried out for the SARS-CoV-2 pandemic, the incidence of KD was significantly reduced in Taiwan. Is KD a preventable disease?